Given the line passes through the point ( -3, 4).

Then, we will write the equation of the line:

y-y1 - m (x-x1) where (x1,y1) is any point passes through the line and m is the slope.

==> y -4 = m ( x+3)

Now we need to determine the...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given the line passes through the point ( -3, 4).

Then, we will write the equation of the line:

y-y1 - m (x-x1) where (x1,y1) is any point passes through the line and m is the slope.

==> y -4 = m ( x+3)

Now we need to determine the slope m.

But, we know that the line is parallel to the line 2y-4x + 2 = 0

Then the slopes are equal.

We will write the equation into the slope form.

==> 2y= 4x -2

==> y= 2x -1

Then the slope is m = 2

We will substitute into the equation of the line.

==> y-4 = 2 ( x+3)

==> y-4 = 2x + 6

**==> y= 2x + 10**